Gripping Device Development: Some Aspects (Journal of Universal Science Research, 2024)
Grippers give robots flexibility and functionality, allowing them to effectively perform a variety of tasks depending on the application context. Among other things, they allow robots to solve the following tasks: capturing objects; moving objects; assembly and installation; work in hazardous environments; maintenance and repair; medical surgery; research in science and engineering, etc. In this article, the authors propose the gripper kinematic diagram development, calculation of the compression force, as well as modeling of the gripping device.